Application of tungsten as a carbon sink for synthesis of large-domain uniform monolayer graphene free of bilayers/multilayers1. Issue 11 (21st March 2015) - Fang, Wenjing; Hsu, Allen; Shin, Yong Cheol; Liao, Albert; Huang, Shengxi; Song, Yi; Ling, Xi; Dresselhaus, Mildred S.; Palacios, Tomas; Kong, Jing
<x xml:space="preserve">Abstract</x> We have found that tungsten (W) foils can be used for controlling the carbon diffusion within copper (Cu) enclosures to synthesize large-domain bi-/multi-layer-free monolayer graphene via chemical vapor deposition.